The relationship between nutritional intake with the incidence of Chronic Energy Deficiency (CED) of teenagers in urban and rural areas - Hariyanti, Lusiana Pradana; Febrinasari, Ratih Puspita; Sari, Yulia (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2025)
ABSTRAK Latar Belakang: Kurang energi kronis (KEK) adalah kondisi kekurangan energi dan protein dalam jangka waktu lama yang umumnya terjadi pada remaja putri atau Wanita Usia Subur. Masalah ini perlu mendapat perhatian karena dapat menimbulkan dampak serius dalam jangka panjang.  Kondisi ini menonjol pada remaja putri usia 15-19 tahun dan dapat diidentifikasi melalui pengukuran lingkar lengan atas (LILA) <23,5 cm. Asupan zat gizi yang tidak memenuhi mencukupi merupakan faktor langsung penyebab KEK, yang dapat menyebabkan penurunan berat badan, dan jika berkelanjutan berisiko memperparah kondisi KEK.Tujuan:  Menganalisis hubungan asupan zat gizi terhadap kejadian kurang energi kronis pada siswi SMA di wilayah urban dan rural Kabupaten Kediri.  Metode: Metode penelitian yang digunakan yaitu observasional analitik dengan design case control, sampel terdiri dari enam SMA yang dibagi menjadi tiga SMA di wilayah urban dan tiga SMA di wilayah rural dengan total sampel 144 siswi masing-masing sekolah 24 sampel.  Pengumpulan data menggunakan kuesioner food recall 2x24 jam yang diambil pada saat weekday dan weekend. Analisis data menggunakan SPSS dengan chi-square.Hasil: Hasil penelitian menunjukkan hubungan yang signifikan antara asupan zat gizi pada wilayah urban asupan energi (p=0,000), protein (p=0,03), karbohidrat (p=0,000) dan lemak (p=0,04) dan wilayah rural asupan energi (p=0,000), protein (p=0,018), karbohidrat (p=0,000) dan lemak (p=0,018) dengan kejadian kurang energi kronis pada siswi SMA di Kabupaten Kediri. Kesimpulan: Asupan zat gizi (asupan  energi, protein, karbohidrat dan lemak) sebagai penyebab kurang energi kronis (KEK) sehingga dapat dijadikan acuan untuk mencegah mengalami kurang energi kronis.  KATA KUNCI: asupan zat gizi; kurang energi kronis; siswi; SMA    ABSTRACTBackground: Chronic energy deficiency (CED) is a condition in teenage girls or women of reproductive age who are experiencing long-term energy and protein deficiencies. CED is still a nutrition problem in teenagers that must be addressed because it has serious long-term impacts. The most prominent CED occurs at the age of 15-19 years, especially in adolescent girls. CED can be seen from the size of the upper arm circumference (MUAC) <23.5 cm Nutritional intake is a direct factor that causes CED. Lack of nutritional intake that does not meet needs can result in weight loss and if it continues can result in chronic energy deficiency. Objectives:  to analyze the relationship between nutritional intake and the incidence of chronic energy deficiency in female high school students in urban and rural areas of Kediri Regency.Methods: The research method used is analytical observational with case control design, the sample consists of six high schools which are divided into three high schools in urban areas and three high schools in rural areas with a total sample of 144 students, each school has 24 samples. Data collection used a 2x24 hour food recall questionnaire taken on weekdays and weekends. Data were analyzed using SPSS Version 26 with chi-square.Results: The results showed that there is a relationship between Nutrient intake in urban areas (energy intake (0.000), protein (0.03), carbohydrates (0.000 and fat (0.04)) and rural areas (energy intake (0.000), protein (0.018), carbohydrates (0.000 and fat (0.018) with the incidence of chronic energy deficiency in female high school students in Kediri Regency Conclusions: Therefore, female students can know that nutritional intake (energy, protein, carbohydrate and fat intake) is the cause of chronic energy deficiency (CED) so that it can be used as a reference to prevent experiencing chronic energy deficiency.  KEYWORD: nutrient intake; chronic energy deficiency; female students; high school